Current trends of state regulation of employment in Ukraine - Ivanchenco, Andrii (Management and Entrepreneurship: Trends of Development, 2018)
Purpose. The urgency of the topic under the study is that socially oriented model of economic development chosen by Ukraine, as evidenced by the realities of life, is mainly not actualized. This is manifested in the ineffectiveness of the mechanisms of state regulation, the lack of formation of a significant number of infrastructure elements of the civilized market or ineffective interaction and distortion of modern society’s social values. This is especially true of labor market, which not only overlaps the interests of workers and employers, but also reflects all social and economic, political, demographic and other processes that take place in the society. The purpose is to study the current trends of state regulation of employment in Ukraine and to substantiate the directions of unemployment reduction. The subject under the study is theoretical aspects of employment, principles and methods of its state regulation.Design/methodology/approach. In the research general scientific methods and principles are used: system analysis, structural and functional analysis, abstract logical method, generalization method. The informational portal of State Statistics Service of Ukraine and State Employment Service were used as a source of data on current national trends in the labor market in relation to employment and unemployment, and the corresponding level of state regulation of employment.Findings. As a conclusion, it is noted that the increase of labor market regulation efficiency is possible only if the interests of entrepreneurs, employees and the state are closely coordinated. There have been substantiated the directions of social dialogue’s improvement and strengthening of population’s motivation to work in the legal sector of the economy, the formation of modern mechanism for providing employment of the population, which would ensure the interests’ consistency of population segments and balance of social development.Research limitations/implications. The scientific significance of the work is to identify the current peculiarities of labor market formation and state regulation of employment and possibilities of practical use of substantiated ways of reducing unemployment.Originality/value. The practical value of the study results is that they should be the basis of comprehensive measures of state authorities for improving regulation of employment in Ukraine.